Pathogenic mechanisms of invasive group A Streptococcus infections by influenza virus–group A Streptococcus superinfection. (25th March 2018) - Okamoto, Shigefumi; Nagase, Satoshi
ABSTRACT: Group A Streptococcus (GAS) are pathogenic bacteria of the genus Streptococcus and cause severe invasive infections that comprise a wide range of diverse diseases, including acute respiratory distress syndrome, renal failure, toxic shock‐like syndrome, sepsis, cellulitis and necrotizing fasciitis. The essential virulence, infected host and external environmental factors required for invasive GAS infections have not yet been determined. Superinfection with influenza virus and GAS induced invasive GAS infections was demonstrated by our team in a mouse model, after which clinical cases of invasive GAS infections secondary to influenza virus infection were reported by other investigators in Japan, USA, Canada, UK China, and other countries. However, the pathogenic mechanisms underlying influenza virus‐GAS superinfection are not yet fully understood. The present review describes the current knowledge about invasive GAS infections by superinfection. Topics addressed include the bacteriological, virological and immunological mechanisms impacting invasion upon superinfection on top of underlying influenza virus infection by GAS and other bacteria (i.e., Streptococcus pneumoniae and Staphylococcus aureus ). Future prospects are also discussed.